Tourniquets in Major Extremity Trauma. Issue 10 (October 2020) - Fuchs, Susan
Abstract : Abstract: Much has been learned about hemorrhage control using tourniquets from wartime experiences, and recent mass casualty events. The use of tourniquets for extremity hemorrhage is a lifesaving skill for all providers to learn.